Formulation of Coalition Threshold For Political Parties Based on Proportionality Principles In The Presidential Election Post Constitutional Court Decision No. 62/PUU-XXII/2024 - Adi Nugroho, Harimurti; Djunaedi, O.; Ismail, Ismail (Asian Journal of Social and Humanities, 2025)
This research aims to formulate a maximum threshold for political party coalition membership based on proportionality principles to prevent dominance. Research findings indicate that in Indonesia's positive legal system, particularly regarding presidential elections, there are no legal norms explicitly defining political party coalition dominance in presidential candidate nominations. Article 6A of the 1945 Constitution does not directly address this matter but implicitly regulates the limitation of absolute dominance through a "two candidate pairs" mechanism in the second round, preventing all parties from joining a single coalition. Law Number 7 of 2017 on Elections also provides no explicit definition, though Article 229 Paragraph (2) implies prevention of nomination monopoly by a single coalition. Theoretically, political party coalition dominance can occur macroscopically (power concentration by large coalitions) and microscopically (internal domination by majority parties within coalitions). In the macroscopic context, dominance includes the formation of large coalitions that dominate the presidential nomination process, while in the microscopic context, dominance occurs when one political party within the coalition has excessive influence over joint decisions. To prevent this, a normative formulation of maximum coalition membership thresholds based on proportionality principles is proposed. Two alternative maximum threshold percentages are proposed: 25% or 50% of the total number of political parties participating in the election.